Perforated sigmoid colon cancer presenting as an incarcerated inguinal hernia: A case report - Sabra, Hassan (Int J Surg Case Rep, 2020)
BACKGROUND: Inguinal hernias are common among the population and usually contain part of the omentum or small bowel, however, other unusual contents have been reported. We report a case of a patient who presented for an incarcerated left inguinal hernia and was found to have an underlying perforated sigmoid cancer. SUMMARY: An 87 years old man presented with typical signs of an incarcerated left inguinal area. During surgery, we dissected free a herniated hard inflammatory mass until it was found to be covering an underlying perforated sigmoid tumor. Inguinal hernia is a common condition affecting many individuals, and colorectal cancer is one of the rare contents reported inside these hernias. Due to the rarity of such a presentation, the surprise encounter during groin surgery may lead to suboptimal treatment. Perforated colorectal cancer, like in our case, may signify a more aggressive disease, and hence a correct diagnosis is crucial to improve outcomes. When underlying colon cancer is suspected during hernia surgeries, proper exploration and oncologic resection might be the optimal choice. CONCLUSION: Surgeons should keep the possibility of underlying colorectal cancer in mind when operating on inguinal hernias and opt for oncologic resection of the identified tumor along with proper lymph node dissection.